2023
DOI: 10.2196/44486
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Family Health and Frailty With the Mediation Role of Health Literacy and Health Behavior Among Older Adults in China: Nationwide Cross-Sectional Study

Abstract: Background Family health develops from the intersection of the health of each family member and their interactions and capacities as well as the family’s internal and external resources. Frailty is the most prominent and typical clinical manifestation during population aging. Family health may be effective in addressing frailty, and this association may be mediated by health literacy and health behaviors. Until now, it is unclear whether and how family health affects frailty in older adults. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…Results showed that 4.1% of participants in Chinese communitydwelling older adults were frail, and 31.0% were pre-frail, which was similar to Li's study (37), but lower than the findings reported in other previous studies (38)(39)(40). Differences in the tools used for assessing frailty may explain this variation (31).…”
Section: Discussionsupporting
confidence: 50%
“…Results showed that 4.1% of participants in Chinese communitydwelling older adults were frail, and 31.0% were pre-frail, which was similar to Li's study (37), but lower than the findings reported in other previous studies (38)(39)(40). Differences in the tools used for assessing frailty may explain this variation (31).…”
Section: Discussionsupporting
confidence: 50%
“…The findings from this database will provide valuable guidance to policymakers and healthcare institutions in formulating more targeted policy recommendations to enhance the physical and mental well-being of Chinese residents post-pandemic. In 2022, a cross-sectional study was conducted to investigate the psychology and behavior factors of Chinese residents, resulting in significant research findings(Li et al, 2023). It is anticipated that the forthcoming study in 2023 will further contribute to the well-being of the Chinese population and global health, as well as advance research in the health field.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a cross-sectional survey study conducted among 723 adult residents in Chongqing communities has demonstrated that regular breakfast consumption may signi cantly lower the relative likelihood of developing frailty 48 . Research among 3758 participants aged ≥ 60 has reported that having breakfast daily, as a potential mediator, contributes to a decrease in the risk of prefrailty and frailty 49 . Importantly, breakfast skippers showed a higher odds ratio for frailty than daily breakfast consumers, and they were characterized by lower dietary intake and poorer nutrient density than daily breakfast consumers 50 .…”
Section: Discussionmentioning
confidence: 99%